Chemical Analysis of a Fodder Tree Leaves (Millettia auriculata) - RAWAT, SHIWANI; SINGH, C.P.; RAWAT, G.S. (Asian Journal of Chemistry, 2010)
Protein, crude protein, ether extract, crude fibre, ash insoluble silica, carbohydrate, sugar, reducing sugars, minerals, trace elements and amino acids were found in the leaves of the Millettia auriculata plant.